Platone e gli Eleati (I) - Lucarini, Carlo M. (Hyperboreus, 2017)
The second part of Plato’s Parmenides (Parmenides’ reasoning, which starts from two opposite hypotheses – that One exists and that One does not exist) contains a number of fallacious arguments which are a signal to the reader that Parmenidean logic inevitably involves contradictions and absurdities. Plato does not explicitly point out in the Parmenides how these difﬁculties are to be resolved, but in his later Sophist demonstrates that only the assumption of the existence of Platonic εἴδη can save the logic of the relationship between One and Many from such absurdities. The reason why he treats Parmenides’ teaching so disrespectfully in the Parmenides is his hostility to the eristic kind of argumentation which, in his view, descends from Parmenides, a primitive dialectician (Dionysodorus’ captious arguments in the Euthydemus often entail the same logical errors as Parmenides’ reasoning in the homonymous dialogue). In spite of this interpretation of Parmenides’ philosophy as having such an infamous association, Plato acknowledges Socrates’ and his own debt to the Eleatic school: both the assumption of an intelligible world and the hypothetico-deductive method of reasoning originate in Eleaticism, and Plato shows his awareness of this.